The level of plasma homocysteine in patients with non-alcoholic fatty liver disease in combination with type 2 diabetes - V. F. Orlovskiy; N. G. Kuchma; A. V. Orlovskiy; N. O. Murenets (Zaporožskij Medicinskij Žurnal)
Non-alcoholic fatty liver disease (NAFLD) is one of the major causes of chronic diseases of the hepatobiliary zone.